Melanoma awareness and prevalence of dermoscopic examination among internet users: a cross-sectional survey - Kaminska-Winciorek, Grazyna; Wydmanski, Jerzy; Gajda, Maksymilian; Tukiendorf, Andrzej (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
Introduction : Melanoma presents the greater threat to health the later the disease is detected and treated, although treatment results can be improved by the widespread use of dermoscopy. However, scarce data are available concerning the awareness of dermoscopy and the frequency of its performance in the non-patient population. Aim: To assess the awareness of melanoma detection by dermoscopic examination among the audience of a scientific website. Material and methods : Respondents were invited to participate in an online cross-sectional survey. They were asked to complete an online questionnaire designed by the authors. The preliminary analysis of 5,154 collected forms and the exclusion of incomplete forms yielded 4,919 fully completed questionnaires; the resulting database was analyzed statistically using logistic regression with the R software program (95% CI). Results: Less than two-fifths (39.2%) of respondents reported ever having sought the advice of a medical professional (dermatologist or other specialist), and 25.4% of the respondents had undergone dermoscopy at least once in their life. Furthermore, approximately one-tenth of respondents (10.7%) were not aware of this detection tool. The study respondents gained knowledge about dermoscopic examination from television and magazines. The performance of dermoscopy was more increasingly associated with inhabitants of larger locales, the use of higher-SPF sunscreens, and greater awareness of the relationship between the risk of melanoma and sunburn. Conclusions : Awareness of melanoma and sun care varied within the analyzed population. A subset of individuals at high risk of melanoma was identified. This group included those who engaged in risky sun exposure behaviors and who had never been examined by dermoscopy.